The Role of Emotioncy in Cognitive Load and Sentence Comprehension of Language Learners - Nazanin Azamnouri (Issues in Language Teaching, 2020)
Emotion and cognition are both considered influential factors in language learning. In this study, the role of "emotioncy" (which is a combination of emotion and frequency) in the cognitive load and sentence comprehension of a group of language learners was examined. Emotioncy includes emotions that are evoked by the senses. To this aim, 200 English as a foreign language (EFL) learners were asked to fill out the NASA Task Load Test, a sentence comprehension test, and an emotioncy scale. Confirmatory factor analysis (CFA) was run to measure the construct validity of the emotioncy scale. Subsequently, Pearson Product-Moment correlation coefficient and structural equation modeling (SEM) were used to analyze the data. The results showed that emotioncy has a significantly negative and positive relationship with cognitive load and sentence comprehension, respectively (p